ANALISA UNTUNG-RUGI MELAKUKAN REVALUASI ASET TETAP DARI ASPEK PAJAK DAN KEUANGAN - IRWAN IRWAN (Media Bisnis, 2014)
Lively occur in the force and in the new PSAK implementation in 2012 that leaned to the IFRS (International Financial Reporting Standards). One interesting aspect to be explored is the PSAK No. 16 on fixed assets using the fair value that would be used to adjust to the IFRS standards. Of course, necessary to apply the fair value revaluation of assets. Another factor that causes revaluation of fixed assets is inflationary conditions that cause the book value does not reflect the prevailing market price and up to date. In asset revalued to match the required market value of the additional costs, among others, the final income tax at the rate of 10% on the excess over fair value or market value less the value of the fiscal book. The assets have been revalued unwavering within 5 years, if transferred will be charged an additional income tax of 15% more than the difference in revaluation has been charged to tax, unless transferred to the government, to combine, consolidation and expansion of business.